KUALITAS PELAYANAN PEMBUATAN PASPOR DI KANTOR IMIGRASI KELAS I SEMARANG - Denny, Denny; Mustam, Moch. (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Nowadays, quality of service become issues that keep occur in some publik services. We can see as there are complaints from people in mass media that they dont get an optimal service, it lead to emerge of bad image for the aparatus. Goal of this reasearch is to know and analyze whether the qualty of service in imigration first class semarang already surpass the expectation. Research use three components morgan and murgatroydâ€™s theory that is, â€œthe triangel of balance in service qualityâ€ which are interpersonal component, procedure environment or process component, and technical or profesional component to make a better service. In practice, we can categorize is with dimensions in quality of services, tangibel, reliability, responsiviness, assurance, empathy. Reasearch use qualitative method. Reasearch try to understand public services management and effect from analyzing quality of service in process of making passport at imigration in semarang. The result indicates that the employees showed good attitude and friendly to customer, friendly attitude and smiles from the employees made the process is not awkward and better in service. The result shows that the customer felt comforable for the waiting room. However, the parking lot at the imigration class I in semarang is not big enough to contain all the customer. Based on the research about quality of service in process of making passport at immigration class I in semarang. Researcher concludes that thereâ€™s some room to improve in the passport service done by imigration first class in semarang.